Analisis Faktor-Faktor yang Mempengaruhi Korupsi dan Modus Korupsi APBD di Malang Raya - Bahri, Syamsul (Jurnal Manajemen Akuntansi dan Bisnis, 2008)
: Corruption has been widely discussed in many form. Public budget (APBD) corruption is abuse action public budget to private or their groups interst. Many factor caused corruption, about: individual behaviour, government organization, law enforcement, and controling. The objective of this study are to obtain empirical evidences and to test factors that effec APBD corruption in Malang Raya.The hyphotesis are tested using the partial regression and multiple regression. The sample in this risearch are Civil Organization such as NGO, public figure, public organization, student, academic ect, amount 165 respondent. The result of study show that as partial individual behaviour not significant effect, government organization significant effect, law enforcement significant effect, and controlling significant to APBD corruption occured. The test used multiple regression support test used partioan regression. Keywords:Â Â  Individual Behaviour, Government Organzation, Low Enforcement, Controlling, APBD Corruption, and Modus APBD Corruption.